A rare skin disorder and its management during pregnancy: epidermolysis bullosa: a case report and literature review. (18th April 2012) - Sokhal, P; Syed, S; Phelan, L; Teoh, TG
Abstract : Epidermolysis bullosa (EB) encompasses a rare group of genetic disorders characterised by extreme skin fragility and blistering in response to minor trauma. Its spectrum of clinical phenotypes range from near-normal life quality with minor blistering, to severe disability with extensive bullosis, scarring, contractures and reduced life expectancy. Pregnancy in those with EB is uncommon and poses significant challenges to the obstetrician, anaesthetist and dermatologist. We report a new case of maternity in a 26-year-old Caucasian with inherited EB, its uncomplicated antenatal course and delivery by elective caesarean section. To date, eleven cases of successful childbirth in women with EB have been documented. Of these, five had vaginal deliveries, two of which had successive deliveries; and six underwent caesarean section. Frequently occurring complications were anaemia, malnutrition, bullous ulceration of the lower abdomen secondary to gravid distension, and trauma to the nipple area following breastfeeding. Only one case was reported to have bulla form at the site of surgical incision and all vaginal deliveries, including those episiotomised, were without urogenital mucosal complications. Based on comprehensive literature review we present recommendations for the management of EB in pregnancy. Multi-disciplinary collaboration, pre-assessment and holistic approaches are vital. The underlying tenets of care for all patients are avoidance of blistering and prevention of secondary infection. These are achieved by padding of the skin where appropriate and the use of non-adhesive dressings. Severe anaemia and chronic infection should be treated early and evidence supports the safe use of regional anaesthesia during labour and/or at caesarean section.